(untitled) (Scientific journal of the Fergana State University, 2026)
The article examines the formation and development of Sufism, as well as the emergence of tariqahs, which spread throughout the Muslim populations of both Eastern and Western countries. Over the centuries, Sufi orders (tariqahs) developed not only as religious communities but also as influential social and political institutions that significantly impacted the shaping of public consciousness, statehood, and cultural norms in various regions of the Muslim world. Particular attention in this article is given to the analysis of key Sufi tariqahs such as Naqshbandiyya, Kubrawiyya, Nimatullahiya, and Yasawiyya, which played a crucial role in the history of the Islamic East — from Central Asia to the Middle East and North Africa.